How do events shape the media agenda on Islam and Muslims in Western Europe? An analysis of news events in Germany, the UK and France (2000–2020) - Liriam Sponholz; Anna-Maria Meuth (Social Sciences and Humanities Open)
Previous research has shown that Western news media often portray Islam and Muslims in a negative light. However, negativity is an inherent feature of media logic. Defining Islam and Muslims as the problem e.g. the “bad news”, in turn, is neither inherent to media logic nor a natural consequence of events. This study attempts to shift the focus from the valence of media representations to the interplay between media attention and problem definition by analysing whether and how events trigger media attention on Muslims and change the media agenda. To answer this question, an automated quantitative content analysis was conducted on all articles of at least 50 words mentioning Islam∗ or Muslims∗ in broadsheets from the UK, Germany and France published between 2000 and 2020 (N = 262,105). This database permitted a time series analysis to determine a) when the issues of Islam and Muslims received (no) attention and b) what events led to the “ups” or peaks in attention. Following that, a co-occurrence network analysis of the term “Muslim” based on the media data before and after a trigger event identified c) how “ups” and “downs” shape media agenda on Islam. The results show that media attention on Islam and Muslims is highly unevenly distributed and concentrated in the aftermath of single terrorist attacks, rather than on religiously motivated terrorist attacks in general. Furthermore, these triggering terrorist attacks lead to a convergence of the media agenda and an essentialisation of Islam and Muslims.